Narrative Analysis of Reporting Tribunnews.com and Asumsi.co In Sexual Harassment News at Universitas Sriwijaya - Fitri Julaika , Amelia; Junaedi, Fajar (Jogjakarta Communication Conference (JCC), 2023)
This research raises how the media reports on sexual violence at Universitas Sriwijaya. Sexual violence on campus is a sensitive issue in Indonesia. There are two media examined in this study, Tribunnews.com and Asumsi.co. This study uses narrative analysis from Algreidas Greimas. The results of this study indicate that journalists as narrators have not placed themselves on the victim's side. Journalists try to be neutral in the narrative structure of the news. This impartial narrative makes the news, not in favour of the victim.